2010
DOI: 10.1097/mbp.0b013e328337cf02
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ambulatory arterial stiffness index with blood pressure response to exercise in the early stages of hypertension

Abstract: EBPR constitutes a sign of premature cardiovascular stiffening in the setting of uncomplicated hypertension. The close relationship between EBPR and PWV but not AASI enhances the concept of PWV as a superior measure of arterial stiffness and constitutes an important factor in the interpretation of EBPR-linked cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
0
20
2
Order By: Relevance
“…Previous studies have shown that arterial stiffness is associated with an exaggerated BP response to exercise, obesity, IR, 30 and poor CRF. 12,31 One factor typically observed in individuals with IR and/or abdominal fat accumulation is a decrease in NO bioavailability, which could be the result of increased blood glucose and free fatty acid concentrations and an increased superoxide production by adipocytes. 32 This impairment could also be related to inflammation with visceral fat producing several proinflammatory cytokines 14 or the result of an inappropriately elevated cyclic GMP stimulated by NO, therefore impairing vasodilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that arterial stiffness is associated with an exaggerated BP response to exercise, obesity, IR, 30 and poor CRF. 12,31 One factor typically observed in individuals with IR and/or abdominal fat accumulation is a decrease in NO bioavailability, which could be the result of increased blood glucose and free fatty acid concentrations and an increased superoxide production by adipocytes. 32 This impairment could also be related to inflammation with visceral fat producing several proinflammatory cytokines 14 or the result of an inappropriately elevated cyclic GMP stimulated by NO, therefore impairing vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, the specific contribution of abdominal adiposity to exercise BP (after control for relevant covariates, including CRF) remains unclear, but some authors have suggested that this relationship could be related to arterial stiffness, a phenomenon caused by inflammation. [12][13][14] Although some studies have suggested an association between insulin resistance (IR) and an increase in BP during exercise, 15 discordant findings have been reported in the literature. For instance, some have observed a strong relationship between IR and exercise BP, 12,16 and others have reported modest increases in exercise DBP with increases in IR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Tsiachris et al [12] reported that exaggerated BP response during exercise is associated with increased arterial stiffening in untreated hypertensive patients, there has been no such study in the normotensive (BP < 120/80 mmHg) population. Because the normotensive population with exaggerated BP response during exercise represents those with higher risk of future development of hypertension, finding of increased arterial stiffness in this group would suggest that arterial stiffness may precede the development of hypertension or at least be present at the very early stage of hypertension.…”
Section: Introductionmentioning
confidence: 96%
“…Ambulatory arterial stiffness index (AASI) was calculated as 1 minus this regression slope, as previously described [18]. AASI quantifies the combined short term variations of DBP and SBP, which may partly reflect the degree of arterial stiffness, but which is also affected by the circadian changes in BP.…”
Section: Ambulatory Bp Measurementsmentioning
confidence: 99%